New records of Pseudotachidiidae from South Korea, including a key to species of the Pseudomesochrinae (Copepoda: Harpacticoida) - Kim, Jong Guk; Lee, Jimin; Huys, Rony (Zootaxa, 2021)
Two species of the marine harpacticoid family Pseudotachidiidae (Copepoda) are reported from subtidal sediments in the Southern Sea of Korea. Psammis wellsi sp. nov. (Danielsseniinae) is most closely related to P. longisetosa Sars, 1910 but differs from its European congener in the ventral ornamentation of the female genital double-somite, the dorsal ornamentation of the second abdominal somite in the male, the armature of the proximal endite of the maxillary syncoxa, the relative setal lengths and general shape of the female P5, and the relative length of the inner seta of the male P5 endopodal lobe and P6. The female of Pseudomesochra tatianae Drzycimski, 1968 is redescribed in detail, constituting the only other record of the species since its discovery at the type locality in western Norway. East Asian records of members of the four subfamilies currently recognized in the Pseudotachidiidae are summarized. Published and other records of the 23 described species in the Pseudomesochrinae are collated and their armature patterns of P1–P5 are tabulated and corrected where necessary. Pseudomesochra affinis (Sars, 1920) is removed from its synonymy with P. longifurcata T. Scott, 1902 and formally reinstated as a valid species. An updated female-based key to the 19 valid species of Pseudomesochra T. Scott, 1902 and four species of Keraia Willen & Dittmar, 2009 is presented.